Cancer risk factors associated with historical contraceptive use and breastfeeding duration - Pipit Feriani; Esti Yunitasari; Ferry Efendi; Ilya Krisnana; Rini Ernawati; Reny Mareta Sari; Nurus Safaah (PAGEPress Publications, 2023)
Cancer is the second leading cause of death worldwide. Two prominent factors in this regard are a woman's history of contraceptive use and the duration of breastfeeding. This study aimed to delve into these risk factors and their impact on cancer incidence. The research employed a cross-sectional design involving 125 cancer patients undergoing chemotherapy at Abdul Wahab Sjahranie Hospital in Samarinda, East Kalimantan. This study used a total sampling approach to include all available patients. Data on contraceptive use, breastfeeding duration, and cancer status were collected through a questionnaire and subsequently analyzed using the chi-square test. The study revealed that breast cancer was the most prevalent type, affecting 41.6% of patients. Additionally, more than half of the respondents breastfed for less than two years (52%), while only 48% breastfed for two years or more. Notably, a significant majority (66.4%) had a history of using hormonal contraception. Statistical analysis demonstrated a compelling association between contraceptive history, breastfeeding duration, and cancer incidence (p < 0.001). In summary, the findings highlight a substantial relationship between a woman's history of contraceptive use, the duration of breastfeeding, and the incidence of breast cancer. These results underscore the importance of further research and the development of targeted interventions to better understand and mitigate breast cancer risk factors among women.